Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja Karyawan Melalui Motivasi Kerja sebagai Variabel Intervening pada Pamella Tiga Yogyakarta - Berlian Shinta Nurcahaya; Muhammad Subkhan (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of leadership style and compensation on employee performance with work motivation as an intervening variable at Pamella Tiga Yogyakarta. The population and sample in this study were Pamela Tiga Yogyakarta employees totaling 45 respondents. This research uses a quantitative approach with survey method and data analysis using SmartPLS with Concurrent Validity test, Loading Factor, Average Variane Extracked (AVE), Discriminant Validity, Fornel Larcker, Cross Loading, Reliability, Cronbach Alpha, Composite Reliability, R Square and Hypothesis Testing. The results showed that there was no positive and significant effect of Leadership Style (X1) on employee performance (Y) at Pamella Tiga Yogyakarta, there was a positive and significant effect of Compensation (X2) on employee performance (Y) at Pamella Tiga Yogyakarta, there was a positive and significant effect of Leadership Style (X1) on Work Motivation (Z) at Pamella Tiga Yogyakarta, There is a positive and significant effect of Compensation (X2) on Work Motivation (Z) at Pamella Tiga Yogyakarta, There is a positive and significant effect of Work Motivation (Z) on employee performance (Y) at Pamella Tiga Yogyakarta, There is no positive and significant effect of Leadership Style (X1) on employee performance (Y) mediated by Work Motivation (Z) at Pamella Tiga Yogyakarta, There is no positive and significant effect of Compensation (X2) on employee performance (Y) mediated by Work Motivation (Z) at Pamella Tiga Yogyakarta.